2015
DOI: 10.1002/jor.23117
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix‐blood composite injection reduces post‐traumatic osteoarthritis after anterior cruciate ligament injury in the rat

Abstract: Purpose The objective of this study was to determine if an injection of a novel extracellular matrix scaffold and blood composite (EMBC) after anterior cruciate ligament (ACL) injury would have a mitigating effect on post-traumatic osteoarthritis (PTOA) development in rat knees. Methods Lewis rats underwent unilateral ACL transection and were divided into three groups: 1) no further treatment (ACLT; n = 10), 2) an intraarticular injection of EMBC on day 0 (INJ0; n = 11), and 3) an intra-articular injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
(60 reference statements)
4
31
0
Order By: Relevance
“…The results with this method identified bone loss in the ACL transected knee, suggesting a global response of the bone to joint unloading, which agree with previous reports of bone loss in the medial compartment of the tibial epiphyses with ACL transection (Maerz et al, 2016; Mohan et al, 2016; Proffen et al, 2016). Previous studies suggest that decreases in BV/TV correspond to unloading of the ACL transected limb or due to an inflammatory response that affects bone resorption (Jay et al, 2012; Maerz et al, 2016; Proffen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results with this method identified bone loss in the ACL transected knee, suggesting a global response of the bone to joint unloading, which agree with previous reports of bone loss in the medial compartment of the tibial epiphyses with ACL transection (Maerz et al, 2016; Mohan et al, 2016; Proffen et al, 2016). Previous studies suggest that decreases in BV/TV correspond to unloading of the ACL transected limb or due to an inflammatory response that affects bone resorption (Jay et al, 2012; Maerz et al, 2016; Proffen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The results with this method identified bone loss in the ACL transected knee, suggesting a global response of the bone to joint unloading, which agree with previous reports of bone loss in the medial compartment of the tibial epiphyses with ACL transection (Maerz et al, 2016; Mohan et al, 2016; Proffen et al, 2016). Previous studies suggest that decreases in BV/TV correspond to unloading of the ACL transected limb or due to an inflammatory response that affects bone resorption (Jay et al, 2012; Maerz et al, 2016; Proffen et al, 2016). A limitation of our analysis is that we did not include a sham operated group; however, we previously found that the BV/TV values for the contralateral knees of the ACL transected group were equivalent to the BV/TV means of the sham group using the Whole Compartment Method (Proffen et al, 2016), and therefore the data presented here are from both knees of the ACL transected group only.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Posttraumatic OA in animals often occurs within 1 month to 1 year after injury, with smaller animals developing macroscopic changes in cartilage structure sooner than larger animals. 39 , 49 Furthermore, animal joints can be opened to directly evaluate the integrity of the graft and articular cartilage. For these reasons, animal models have been long used to study ACL injuries, treatments, and associated complications.…”
mentioning
confidence: 99%